An iPSC-based model of 47,XYY Jacobs syndrome reveals a DNA methylation-independent transcriptional dysregulation shared with male X aneuploid cells - Astro, Veronica; Cardona-Londoño, Kelly Yojanna; Cortés-Medina, Lorena Viridiana; Alghamdi, Rawan; Ramírez-Calderón, Gustavo; Kefalas, Fotios; Dilmé-Capó, Jair; Radío, Santiago; Adamo, Antonio (Genome Research, 2025)
Jacobs (JS) and Klinefelter (KS) syndromes, carrying 47,XYY and 47,XXY chromosomes, respectively, are the most prevalent sex-chromosome aneuploidies in males. JS and KS patients share several clinical features, including sterility, hormonal deficits, neurocognitive delay, and skeletal-muscle defects, although the penetrance of these traits in the two syndromes varies. Despite the high incidence, the molecular mechanisms underlying the clinical manifestations in sex aneuploid male patients are still elusive. In this study, we characterize the inaugural cohort of 47,XYY human induced pluripotent stem cells (iPSCs). We perform a comprehensive transcriptional analysis, including 47,XYY and 46,XY primary fibroblasts, iPSCs, and neural stem cells (NSCs), alongside a comparative analysis of 47,XYY and 47,XXY fibroblasts and iPSC transcriptomes. We reveal a transcriptional feedback mechanism tuning non-PAR X Chromosome gene (NPX) homologs in Y supernumerary cells, a phenomenon not detected in X aneuploid male iPSCs. By ectopically modulating the expression of selected NPY genes, we demonstrate a transcriptional link between the UTY–KDM6A gene pair. Furthermore, our analyses identify a shared transcriptomic signature between JS and KS, discernible already at the iPSC stage, with a notable enrichment for processes related to neurological functions. This transcriptomic convergence underscores potential commonalities in the molecular pathways underpinning the pathophysiology of male sex-chromosome aneuploidies. Finally, through genome-wide DNA methylation profiling of JS iPSCs, we demonstrate that a supernumerary Y Chromosome only minimally impacts the methylation status of 47,XYY cells at the pluripotent stage. Our work reveals critical transcriptional feedback mechanisms and shared gene expression signatures in male sex-chromosome aneuploidies.